Matrix Effects on Photoluminescence and Oxygen Sensitivity of a Molecular Ruby. Issue 6 (18th March 2022) - Wang, Cui; Kitzmann, Winald R.; Weigert, Florian; Förster, Christoph; Wang, Xifan; Heinze, Katja; Resch‐Genger, Ute
Abstract: The molecular ruby analogue [Cr(ddpd)2 ] 3+ (ddpd= N, N' ‐dimethyl‐ N, N '‐dipyridine‐2‐ylpyridine‐2, 6‐diamine) exhibits near infrared (NIR) emission with a high photoluminescence (PL) quantum yield Φ PL of 11 % and a lifetime of 898 μs in deaerated water at room temperature. While ligand‐based control of the photophysical properties has received much attention, influences of the counter anions and microenvironment are still underexplored. In this study, the luminescence properties of the molecular ruby were systematically examined for the counter anions Cl −, Br −, [BF4 ] −, [PF6 ] −, [BPh4 ] −, and [BArF24 ] − in acetonitrile (MeCN) solution, in crystals, and embedded into polystyrene nanoparticles (PSNP). Stern‐Volmer analyses of the oxygen quenching studies in the intensity and lifetime domain showed the highest oxygen sensitivity of the complexes with the counter anions of [BF4 ] − and [BArF24 ] −, which also revealed the longest luminescence lifetimes. Embedding [Cr(ddpd)2 ][PF6 ]3 in PSNPs and shielding with poly(vinyl alcohol) yields a strongly NIR‐emissive oxygen‐insensitive material with a record Φ PL of 15.2 % under ambient conditions. Abstract : Second sphere effects : Counter anions can significantly impact the luminescence of cationic complexes by suppressing or inducing non‐radiative decay pathways. The near‐infrared (NIR) emissive [Cr(ddpd)2 ] 3+ complex showed strongly varying luminescence quantum yields ( Φ PL ) and lifetimes depending on the counter ions and the surrounding matrix. Embedding polystyrene nanoparticles stained with the complex in a poly(vinyl alcohol) film yielded a strongly NIR‐emissive material with Φ PL of 15.2 % under ambient conditions.